Ultrafine FeF3·0.33H2O Nanocrystal-Doped Graphene Aerogel Cathode Materials for Advanced Lithium-Ion Batteries - He, Dafang (Langmuir : the ACS journal of surfaces and colloids, 2023)
FeF3 has been extensively studied as an alternative positive material owing to its superior specific capacity and low cost, but the low conductivity, large volume variation, and slow kinetics seriously hinder its commercialization. Here, we propose the in situ growth of ultrafine FeF3·0.33H2O NPs on a three-dimensional reduced graphene oxide (3D RGO) aerogel with abundant pores by a facile freeze drying process followed by thermal annealing and fluorination. Within the FeF3·0.33H2O/RGO composites, the three-dimensional (3D) RGO aerogel and hierarchical porous structure ensure rapid diffusion of electrons/ions within the cathode, enabling good reversibility of FeF3. Benefiting from these advantages, a superior cycle behavior of 232 mAh g-1 under 0.1C over 100 cycles as well as outstanding rate performance is achieved. These results provide a promising approach for advanced cathode materials for Li-ion batteries